An Experiential Aged Care Module for First-Year Undergraduate Medical Students - Deepa Alex; Yatinesh Kumari; Amudha Kadirvelu (MDPI AG, 2021)
A rapid demographic transition to aging populations is imminent over the next decade, especially in Southeast Asian countries. An aging population presents a host of medical challenges, such as multimorbidity; chronic illnesses; and geriatric syndromes, such as frailty, falls, dementia, and incontinence. In order to tackle such issues efficiently, there is an urgent need to train future doctors in geriatric medicine. Aged care is a specialty in medicine that was not traditionally part of the undergraduate medical curriculum. With the changing demographic, aged care content needs to be integrated into the existing curriculum for undergraduate medical students. In this paper, we present an introductory novice level geriatric module that was developed for first-year medical undergraduate students in Monash University, Malaysia. The module consisted of collaborative active learning sessions on healthy aging, interaction with older adults from the community, and a simulated experiential activity. Feedback was collected from students on module completion. The immediate impact of the module was positive from the student responses. The findings from this study will be useful to inform the development and implementation of future educational interventions for aged care, as well as to support the establishment of a vertically integrated aged care curriculum, in order to prepare future doctors to provide healthcare for the ageing Asian population.